A World-First Surgical Instrument for Minimally Invasive Robotically-Enabled Transplantation of Heart Patches for Myocardial Regeneration: A Brief Research Report - Roche, Christopher David; Zhou, Yiran; Zhao, Liang; Gentile, Carmine (Frontiers in Surgery, 2021)
Patch-based approaches to regenerating damaged myocardium include epicardial surgical transplantation of heart patches. By the time this therapy is ready for widespread clinical use, it may be important that patches can be delivered via minimally invasive and robotic surgical approaches. This brief research report describes a world-first minimally invasive patch transplantation surgical device design enabled for human operation, master-slave and fully automated robotic control. METHOD: Over a 12-month period (2019-20) in our multidisciplinary team we designed a surgical instrument to transplant heart patches to the epicardial surface. The device was designed for use via uni-portal or multi-portal Video-Assisted Thorascopic Surgery (VATS). For preliminary feasibility and sizing, we used a 3D printer to produce parts of a flexible resin model from a computer-aided design (CAD) software platform in preparation for more robust high-resolution metal manufacturing. RESULTS: The instrument was designed as a sheath containing foldable arms, less than 2 cm in diameter when infolded to fit minimally invasive thoracic ports. The total length was 35 cm. When the arms were projected from the sheath, three moveable mechanical arms at the distal end were designed to hold a patch. A rotational head allowing for the arms to be angled in real time, a surface with micro-attachment points for patches and a releasing mechanism to release the patch was included. CONCLUSION: This brief research report represents a first step on a potential pathway towards minimally invasive robotic epicardial patch transplantation. For full feasibility testing, future proof-of-concept studies and efficacy trials will be needed.